Validity for the Assessing Classroom Sociocultural Equity Scale (ACSES) in Early Childhood Classrooms. Issue 2 (17th February 2020) - Curenton, Stephanie M.; Iruka, Iheoma U.; Humphries, Marisha; Jensen, Bryant; Durden, Tonia; Rochester, Shana E.; Sims, Jacqueline; Whittaker, Jessica V.; Kinzie, Mable B.
ABSTRACT: Research Findings : The purpose of this study was to refine and validate the Assessing Classroom Sociocultural Equity Scale (ACSES), an observation tool for measuring equitable sociocultural interactions in early childhood classrooms (pre-K to Grade 3) with racially minoritized learners (RMLs). Preliminary psychometric information from 142 observations across 52 teachers (average of 2 videos per teacher) provided internal consistency and validity information. Our analyses resulted in a significant and highly reliable 5-factor solution comprising 33 items. These five factors are: Challenging Status Quo Knowledge, Equitable Learning Opportunities for RMLs, Equitable Discipline, Connections to Home Life, and Personalized Learning Opportunities . Concurrent and divergent validity between ACSES and the Classroom Assessment Scoring System (CLASS) indicated these factors are associated with distinct aspects of classroom interactions. Lastly, correlations between teacher socio-demographic (age and race/ethnicity) and professional (years teaching, education, and major) characteristics and ACSES factor scores were considered. Practice or Policy : Results are discussed in relation to research contributions of the measure as well as pre-service education and in-service professional development for teachers.